ANALISIS RASIO KESEHATAN BANK (CAR) TERHADAP RETURN ON ASSETS PADA BANK-BANK UMUM DI INDONESIA - Tripermata, Lukita; Yeni, Yeni; Hartati, Lesi (Universitas Indo Global Mandiri Palembang, 2023)
This study aims to determine and analyze the effect of Capital Adequacy Ratio on Return on Assets in commercial banks in Indonesia. This type of research is a quantitative descriptive. The sampling technique used purposive sampling. The sample used is 15 commercial banks in Indonesia. The research data is secondary data sourced from the Annual Report of commercial banks in Indonesia. Analysis of the data used in this study using descriptive statistical analysis and regression analysis, as well as the classical assumption test. The test results show that the Capital Adequacy Ratio has a positive and significant effect on Return on Assets at commercial banks in Indonesia.